Розробка системи наведення і стабілізації з нейрорегулятором на основі моделі авторегресії з ковзним середнім - Кузнецов, Борис Іванович; Василець, Тетяна Юріївна; Варфоломієв, Олексій Олексійович (НТУ "ХПІ", 2011)
Виконано синтез системи наведення і стабілізації озброєння легкоброньованих машин і застосування нейромережевого регулятора на основі моделі авторегресії з ковзним середнім. Розроблена схема системи наведення і стабілізації з пропорційним регулятором у контурі положення і нейромережевим регулятором у контурі швидкості. Проведено моделювання системи на ЕОМ і виконано аналіз динамічних характеристик системи

Synthesis of a light-armored vehicle armament guidance and stabilization system is performed with application of a neurocontroller on the basis of an autoregressive moving average model. The neuro-controller architecture and principle of operation are presented. A schematic model of the guidance and stabilization system with a proportional controller in the position loop and a neuro-controller in the speed loop is developed. NARMA-L2 controller is synthesized. Computer simulation is made, the system dynamic behavior analyzed
Synthesis of a guidance and stabilization system with a neuro-controller on the basis of an autoregressive moving average model
Keywords: динамічні характеристики; контур швидкості; системи управління; бойові машини; neuro-controller; autoregressive moving average model; neural guidance; stabilization; NARMA-L2 controller control system; synthesis; analysis